Kebijakan Pertambangan: Regulasi untuk Siapa? - Said, Moh (Jurnal Ilmiah Administrasi Publik, 2017)
The purpose of this papers is to analysis role of state in the mining policy in Indonesia. Tulisan ini menganalisis peran negara dalam kebijakan pertambangan di Indonesia. Liberalisation in mining will debilitate state ideals. This country has clearly set in the Constitution (Undang-Undang Dasar 1945) Article 33 point 3 that the earth,water,and natural resources are controlled by the state and should be utilized as much as possible for the welfare of the people. Today, mining regulation indicates have ignored the mandate of the constitution. Then, actually a mining policy created for whom? This case should use state centered perspective, how is the role of government, regulation, and what is the feasible methodsÂ Â  to answer the basic assumption that mining resources should be utilized as much as for welfare of people. The reality alsoanalyze by political economic perspective.Â